Pendidikan Karakter Perspektif Tafsir Al-Misbah Surah Al- Furqan Ayat 63-70 dan Implikasinya Terhadap Pengembangan Pendidikan Islam - Muhammad Yusuf; Muh. Takdir (Jurnal Fascho: Kajian Pendidikan dan Sosial Kemasyarakatan, 2020)
The purpose of this study was to analyze and describe M. Quraish Shihab's views on character education through the study of the al-mishbah tafsir book. This study used a research library method. Data collection is done by reading, understanding, analyzing, comparing existing data and then grouping them according to their respective characteristics through the Critical Discourse Analysis model. The results of the research show that in Surah Al-Furqan verses 63-70 that actions called character are being wise, generous, not killing people except for reasons justified by syar a' (Islamic law), praying a lot and repenting, and keeping yourself from committing free sex. Meanwhile, the values ??of character education that can be understood are that if good character is conveyed to students continuously and systematically it is able to shape the personality and character of a strong Muslim, so that they can display and apply the values ??of Islamic teachings in their life.